SOSIALISASI PANDUAN KLASIFIKASI DAN KONSTRUKSI KAPAL IKAN FRP KURANG DARI 12 METER DI WILAYAH PESISIR PULAU RAAM - Nurul Huda; Andreas Pujianto; Yani Nurita Purnawanti; Boby Wisely Ziliwu; Rezza Ruzuqi; Ahmad Nurfauzi; Djoko Prasetyo; Bagas Prakoso; Muhfizar Muhfizar; Egbert Joshua Sirait; Pundi Ramadhan Sudrajat (Buletin SWIMP, 2022)
Raam Island is a village located in the city of Sorong, West Papua Province which has several business groups for FRP boat craftsmen, especially for fishing purposes. The standard manufacturing process standards applied by fiber ship craftsmen make the quality of the fabrication results different from each existing shipyard. The socialization activity was carried out by presenting materials directly to shipyard owners and FRP ship craftsmen. BKI as a state-owned company engaged in survey services and ship certification has regulations related to ship construction. In 2020, BKI issued "Guidance for Certification of FRP Fishing Vessel less than 12 m" which is very suitable for the type of ship produced by ship craftsmen on Raam Island. FRP), ship structure design & FRP ship stability, machinery installation, electrical installation, and ship safety equipment. Evaluation is given by giving pre-test and post-test methods to see the progress of participants in understanding the material given. From 10 questions given in the post test, most of the participants have shown significant improvement when compared to the pre test.